Konsep dan Praktik Qanaah di Kalangan Dosen Tasawuf Fusi - Rizki Hidayah Batubara (Medan Resource Center, 2021)
Qanaah is an attitude of accepting enought and full of sincerity towards every gift that Allah Swt has given to him. A person who is qanaah dosn’t just sit idly by and accept the fate that Allah Swt has given, but a person who is qanaah will always try and endeavor to Allah Swt. If someone applies the concept and practice of qanaah then his life will always be calm because in his heart there is only sincerity. Thus the question arises, namely how to realize or practice qanaah in life so that a good qanaah is created. The purpose of this research is to explain about how to realize or practice qanaah in life. The research method used is interviews with Sufism lecturers and is equipped with books related to qanaah. Then, in this study using descriptive qualitative data analysis. The results found are that there are views of permanent lecturers who have different functions but have the understing of this qanaah. The conclusion is then apply the concept because this is a way to be grateful for life